PERANAN INLAND PORT DALAM MENINGKATKAN DAYA SAING NASIONAL - Lies Lesmini; Raden Didiet; Rahmat Hidayat (Institut Transportasi dan Logistik Trisakti, 2018)
The purpose of this study was to analyze the role of inland ports in reducing the total cost and total delivery time of goods. Inland port is an alternative solution to logistics problem, which will ultimately reduce product competitiveness due to high logistics costs. The main power of the inland port is intermodal integration since it could also minimize the processes that are carried out separately when sending goods through conventional ports. The research method used was descriptive qualitative. The data collected in this study was obtained through structured interviews and in depth interviews from several speakers who were important actors in the field of inland ports, along with some data sourced from third parties. The result is that inland ports through intermodal integration are able to reduce total costs, total time and reduce highway density through the transfer of goods from truck to train